2020
DOI: 10.1111/ffe.13339
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on the influence of welding residual stresses on fatigue for two different weld geometries

Abstract: Fatigue tests on welded small-scale specimens often do not show a distinct residual stress influence. An exception is longitudinal stiffeners, which are therefore frequently used to study the influence of welding residual stresses on fatigue. The results are not directly transferable to other weld geometries because the residual stress distribution depends on the weld geometries. In the presented investigation, fatigue tests on multilayer K-butt weld and longitudinal stiffener specimens were performed. The tes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Interesting to observe, however, the slope of the as‐built PBF‐LB/M is steeper for R = −1 than for R = 0, while the opposite is true for the wrought material. This effect can be related to residual stresses in the PBF‐LB/M specimens and is known from tests of welded specimens at different stress ratios; see Friedrich 50 . Furthermore, the shallow slope of the wrought material S–N curve led to a large number of run‐outs for R = −1.…”
Section: Fatigue Tests Of Wrought and Pbf‐lb/m Specimensmentioning
confidence: 89%
See 1 more Smart Citation
“…Interesting to observe, however, the slope of the as‐built PBF‐LB/M is steeper for R = −1 than for R = 0, while the opposite is true for the wrought material. This effect can be related to residual stresses in the PBF‐LB/M specimens and is known from tests of welded specimens at different stress ratios; see Friedrich 50 . Furthermore, the shallow slope of the wrought material S–N curve led to a large number of run‐outs for R = −1.…”
Section: Fatigue Tests Of Wrought and Pbf‐lb/m Specimensmentioning
confidence: 89%
“…This effect can be related to residual stresses in the PBF-LB/M specimens and is known from tests of welded specimens at different stress ratios; see Friedrich. 50 Furthermore, the shallow slope of the wrought material S-N curve led to a large number of run-outs for R = À1. A common way of presenting fatigue test results for different stress ratios is the Haigh diagram.…”
Section: Assessment Of Mean-stress Effect On Fatigue Strengthmentioning
confidence: 99%
“…Meanwhile, the effects of different bending angles and welding paths on RS distribution were compared and analyzed, and the results showed that this method provided valuable reference for engineers and scientists working in the field of RS. Friedrich N et al [18] proposed to reveal the effect of welding RS on the initiation and propagation of fatigue cracks by comparing samples with different weld geometries, and conducting fatigue tests on multi-layer K-shaped butt welds and longitudinal stiffener samples. The results showed that, when there were the same number of cycles, samples in the welded state were more prone to the initiation of macroscopic cracks than those in the stress-relieved state.…”
Section: Related Workmentioning
confidence: 99%
“…However, as is well‐known, the fatigue strength of a welded component in presence of multiaxial cyclic loading is significantly lower than that of an unwelded one (even if the components are made of the same material) 2 . In particular, the factors causing the above strength reduction 3–5 are residual stresses, 6–9 thermal distortions, 10 defects caused by partial penetration, 11 and material microstructural imperfections 12 …”
Section: Introductionmentioning
confidence: 99%
“…1 However, as is wellknown, the fatigue strength of a welded component in presence of multiaxial cyclic loading is significantly lower than that of an unwelded one (even if the components are made of the same material). 2 In particular, the factors causing the above strength reduction [3][4][5] are residual stresses, [6][7][8][9] thermal distortions, 10 defects caused by partial penetration, 11 and material microstructural imperfections. 12 Moreover, complex time variable load histories applied to welded components result in severe stress/ strain gradients at the weld toes/roots leading to fatigue damage near such critical regions.…”
Section: Introductionmentioning
confidence: 99%